Clinical Practice Guidelines for Clostridium difficile Infection in Adults: 2010 Update by the Society for Healthcare Epidemiology of America (SHEA) and the Infectious Diseases Society of America (IDSA) - Cohen, Stuart H.; Gerding, Dale N.; Johnson, Stuart; Kelly, Ciaran P.; Loo, Vivian G.; McDonald, L. Clifford; Pepin, Jacques; Wilcox, Mark H. (Infection Control and Hospital Epidemiology, 2010)

Clinical Practice Guideline by the Infectious Diseases Society of America (IDSA) and Society for Healthcare Epidemiology of America (SHEA): 2021 Focused Update Guidelines on Management of Clostridioides difficile Infection in Adults - Johnson, Stuart; Lavergne, Valéry; Skinner, Andrew M; Gonzales-Luna, Anne J; Garey, Kevin W; Kelly, Ciaran P; Wilcox, Mark H (Clinical Infectious Diseases, 2021)
Abstract This clinical practice guideline is a focused update on management of Clostridioides difficile infection (CDI) in adults specifically addressing the use of fidaxomicin and bezlotoxumab for the treatment of CDI. This guideline was developed by a multidisciplinary panel representing the Infectious Diseases Society of America (IDSA) and the Society for Healthcare Epidemiology of America (SHEA). This guideline is intended for use by healthcare professionals who care for adults with CDI, including specialists in infectious diseases, gastroenterologists, hospitalists, pharmacists, and any clinicians and healthcare providers caring for these patients. The panel’s recommendations for the management CDI are based upon evidence derived from topic-specific systematic literature reviews. Summarized below are the recommendations for the management of CDI in adults. The panel followed a systematic process which included a standardized methodology for rating the certainty of the evidence and strength of recommendation using the GRADE approach (Grading of Recommendations Assessment, Development, and Evaluation). A detailed description of background, methods, evidence summary and rationale that support each recommendation, and knowledge gaps can be found online in the full text.

Clinical Practice Guidelines for Clostridium difficile Infection in Adults and Children: 2017 Update by the Infectious Diseases Society of America (IDSA) and Society for Healthcare Epidemiology of America (SHEA) - McDonald, L. Clifford; Gerding, Dale N.; Johnson, Stuart; Bakken, Johan S.; Carroll, Karen C.; Coffin, Susan E.; Dubberke, Erik R.; Garey, Kevin W.; Gould, Carolyn V.; Kelly, Ciaran; Loo, Vivian; Shaklee Sammons, Julia; et al. (Clinical Infectious Diseases, 2018)
A panel of experts was convened by the Infectious Diseases Society of America (IDSA) and Society for Healthcare Epidemiology of America (SHEA) to update the 2010 clinical practice guideline on Clostridium difficile infection (CDI) in adults. The update, which has incorporated recommendations for children (following the adult recommendations for epidemiology, diagnosis, and treatment), includes significant changes in the management of this infection and reflects the evolving controversy over best methods for diagnosis. Clostridium difficile remains the most important cause of healthcare-associated diarrhea and has become the most commonly identified cause of healthcare-associated infection in adults in the United States. Moreover, C. difficile has established itself as an important community pathogen. Although the prevalence of the epidemic and virulent ribotype 027 strain has declined markedly along with overall CDI rates in parts of Europe, it remains one of the most commonly identified strains in the United States where it causes a sizable minority of CDIs, especially healthcare-associated CDIs. This guideline updates recommendations regarding epidemiology, diagnosis, treatment, infection prevention, and environmental management.

European Society of Clinical Microbiology and Infectious Diseases: 2021 update on the treatment guidance document for Clostridioides difficile infection in adults - Van Prehn, Joffrey; Reigadas, Elena; Vogelzang, Erik H.; Bouza, Emilio; Hristea, Adriana; Guery, Benoit; Krutova, Marcela; Norén, Torbjorn; Allerberger, Franz; Coia, John E.; Goorhuis, Abraham; Van Rossen, Tessel M.; et al. (Clinical Microbiology and Infection, 2021)